Perancangan dan Implementasi RESTful API untuk Aplikasi Mobile Pembelajaran Flora dan Fauna pada Google Cloud Platform - Calista Chandra; Wijaya, Frans; Gunawan, Jason Andrew; Lee, James Rafferty; Maulana, Ade (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
In recent years, there has been an increase in smartphone ownership among school-aged children. This increase was influenced by the Covid-19 pandemic, which caused restrictions on outdoor activities and activity adjustments such as online learning. Even though the Covid-19 pandemic is now over, children spend more time at home with their smartphones. Meanwhile, playing and learning outdoors is very beneficial for their social, emotional, cognitive, and physical development. Therefore, EksFlorasi exists as a solution in the form of a mobile-based educational application to encourage children to explore nature around them and learn about flora dan fauna using their smartphones. To support EksFlorasi, a web API was designed and developed using the waterfall method. The API functions as the mobile app’s back-end component and was built using Node.js with the Express JS framework and implemented REST (REpresentational State Transfer). The RESTful API was then deployed using Google Cloud Platform’s cloud computing services to make EksFlorasi accessible to users across Indonesia with the lowest latency possible. To ensure that the RESTful API functions as intended, the deployment on Google Cloud Platform utilized a combination of Cloud Run, Cloud SQL and Cloud Storage services. Based on the research results, the RESTful API which has been successfully developed and deployed on Google Cloud Platform is functioning well and able to deliver optimal performance for up to 50 concurrent users.